Cell division: modeling in Genetics and Molecular Biology (Research, Society and Development, 2022)
The teaching of genetics and molecular biology carried out at school is still a traditional content-based teaching method, which is often far from the reality of students, and different resources and methods are not used for the implementation of the classroom. The research aimed to analyze the didactic potential that external representations can play in the teaching and learning of "Cell Division" through a pedagogical workshop. For this, it was decided to develop a simple, cheap and practical method using a model didactic in a Biology class to teaching mitosis and meiosis to high school students, contributing to the study and deepening of the structure of chromosomes, in addition to its behavior during mitosis and meiosis. Thus, a practical class was held with students from the 3rd year of the Carolina Silva State School located in the city of Vazante/MG, in order to observe the contribution of this methodology in the teaching-learning process. Data collection is based on bibliographic research, book portals and periodicals, including publications related to this research topic in national and international contexts, in addition to the collection of reports and participant observation. The data indicate that the construction of didactic models can be considered an effective tool for the teaching-learning connection, and constitutes a representative process, using the development of a three-dimensional model of genomic structures. These models are accessible resources that can increase understanding of genetics topics and reduce the level of abstraction through tactile learning.